Silver nanoparticles embedded polyamide nanofiltration membrane for antimicrobial properties - Tengku Nur Anisa, Tengku Sallehuddin (2019)
In nanofiltration and other membrane processes, membrane fouling become a common problem that contributes to a major problem in water filtration. Fouling normally occurs due to natural organic matters like humic acid and various bacteria that already exist in the water. Some common methods like coagulation, flocculation, ion exchange, electrodeposition and extraction were used to remove pollutants from the water and wastewater. However, they encounter disadvantages which required series steps of heterogeneous reactions or substances distribution between different phases that normally require a lengthy operating period. Thin film composite membrane serves a physical barrier that can removes solids, bacteria, viruses and other unwanted molecules in such a better way. Previously, there were several attempts to produce polyamide membrane using different monomers. The aim of this present study was to produce antibacterial polyamide-silver nanofiltration thin film composite membrane using M-phenyldiamine and trimesoyl chloride as monomers on polyethersulfone membrane via interfacial polymerization for humic acid removal. The silver nanoparticles were synthesized from silver nitrate and polyphenols in tea extract was used as reducing agent. Success of silver formation were characterized by UV- Vis spectrophotometer, Transmission Electron Microscopy, X-ray Diffractometer and Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy. Antimicrobial properties of silver nanoparticles were tested against Escherichia coli bacteria. On the membrane preparation part, the variable change such as reaction time can produce good nanofiltration membrane. The effect of reaction time (dipping time) and the addition of silver nanoparticles onto the membrane were investigated. The success of formation of polyamide layer on membrane were determined by analysis of Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy and Field Emission Scanning Electron Miscroscopy. All membranes were characterized in term of chemical structure parameters, pure water permeability, rejection of different charged solutes (sodium chloride and sodium sulphate) and uncharged solute (Vitamin B12) and rejection of humic acid solution. These properties include hydrophilicity (), pore size (rp) and effective thickness over membrane porosity (x/Ak). From the characterization, all polyamide membrane was considered as tight nanofiltration membranes. From the flux-loss analysis, polyamide-silver nanoparticles membrane with 60seconds reaction time exhibited the lowest total flux-loss which is 1.69% in the filtration of humic acid. The addition of silver nanoparticles with concentration of 60x10-3 g/mL onto the membrane slightly gave an effect to the membrane and reduced the fouling. This study will provide a valuable guideline to produce nanofiltration thin film composite membrane that have antibacterial properties for removal of humic acid in the water and wastewater filtration.